2020
DOI: 10.1111/den.13710
|View full text |Cite|
|
Sign up to set email alerts
|

Establishment of an in‐vivo porcine delayed perforation model after duodenal endoscopic submucosal dissection

Abstract: Objectives Duodenal endoscopic submucosal dissection (ESD) for superficial non‐ampullary duodenal epithelial tumors has a significant incidence rate of delayed perforation. Although several methods have been proposed to prevent delayed perforation, the most appropriate methods remain unclear. Currently, there is no appropriate animal model to validate methods for preventing duodenal delayed perforation. This study aimed to establish an in‐vivo porcine delayed perforation model after duodenal submucosal dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Pigs (12–20 kg) from the same farm were used for the experiments. The in vivo porcine delayed perforation model after duodenal ESD is previously described 19 . This model is known to show a 100% delayed perforation rate within several days after successful duodenal ESD.…”
Section: Methodsmentioning
confidence: 99%
“…Pigs (12–20 kg) from the same farm were used for the experiments. The in vivo porcine delayed perforation model after duodenal ESD is previously described 19 . This model is known to show a 100% delayed perforation rate within several days after successful duodenal ESD.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we revealed that a crucial cause of delayed perforation after duodenal ESD is ischemic changes around the mucosal defect [ 14 ], and cell sheet transplantation with omental coverage can promote tissue regeneration to prevent this lethal complication [ 24 ]. While we were unable to evaluate the gene expression profile in our porcine ESD model, the data obtained in our rats strongly suggest that revascularization at the ischemic area from the omentum and improvement of blood flow by cell sheet transplantation play a crucial role in tissue regeneration at the ESD site.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of bile and pancreatic juice and duodenal wall thinness are thought to be the main causes of delayed perforation, so closure of the mucosal defect after ESD is recommended for preventing these complications in clinical practice [ [11] , [12] , [13] ]. In addition to these physiological features of the duodenum, disturbance of the intravascular flow due to extended muscularis propria with endoscopic air supply during ESD and consequent ischemia at the ESD site might be important factors contributing to delayed perforation [ 14 ]. A histological analysis of a porcine duodenal ESD model revealed atrophy of the gland and a ghost-like appearance of the surrounding mucosa at the duodenal ESD site.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hanaoka et al reported that delayed perforation after ESD occurred because of ischemic changes at the ESD site [ 19 ]. In a large animal model, we revealed that ischemia is one of the main causes of delayed perforation after duodenal ESD [ 20 ].…”
Section: Introductionmentioning
confidence: 99%